1993
DOI: 10.1136/jnnp.56.3.274
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral frontal lobectomy can produce strategy application disorder.

Abstract: Following a 5 cm left frontal lobectomy for the removal of a mixed astrocytomaoligodendroglioma, a 51 year old right handed man showed a marked dissociation between his performance on standard neuropsychological tests and his everyday behaviour. In contrast to his intact neuropsychological test performance, he was impaired on a test of "strategy application" which requires goal articulation, plan specification, selfmonitoring, and evaluation of outcomes, as well as the establishment of mental "markers" to trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
60
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 9 publications
5
60
1
1
Order By: Relevance
“…This claim is consistent with both lesion and imaging data. At least five recent case studies (reviewed in Burgess, in press) have presented frontal lobe patients with an anatomical and neuropsychological profile similar to PF (Eslinger & Damasio, 1985;Goldstein, Bernard, Fenwick, Burgess, & McNeil, 1993;Shallice & Burgess, 1991b). Like PF, these patients had difficulty in coping with real-world (ill-structured) situations despite high IQ.…”
Section: Discussionmentioning
confidence: 99%
“…This claim is consistent with both lesion and imaging data. At least five recent case studies (reviewed in Burgess, in press) have presented frontal lobe patients with an anatomical and neuropsychological profile similar to PF (Eslinger & Damasio, 1985;Goldstein, Bernard, Fenwick, Burgess, & McNeil, 1993;Shallice & Burgess, 1991b). Like PF, these patients had difficulty in coping with real-world (ill-structured) situations despite high IQ.…”
Section: Discussionmentioning
confidence: 99%
“…Rule breaks could depend on prospective and retrospective memory, 12,33 as our results confirmed (significant correlation between rule breaks and DRS memory subscale), but also on planning capacities, consideration of internal signals acting as triggers for voluntary changes, and correct reevaluation of goals. 17,33,34 As for the number of subtasks, it could be linked to the inability to strategically plan, organize, and update current information, and to monitor ongoing performance. 33 A study by Alderman et al 35 with brain-injured participants showed 2 patterns of failure (number of rule breaks or failure to initiate tasks) in the simplified version of the Multiple Shopping Errands Test (The Multiple Shopping Errands Test, a ''real-life'' multitasking test carried out in a shopping center, requires the participant to buy specific things, obtain some information, be in a particular place at a particular time, and follow several rules while doing these things 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…15 Studies have shown low correlations between the SET and traditional laboratory executive tests, whereas there are strong correlations between the SET and multitasking deficits in daily life. 17 This suggests that disabilities in situations involving multitasking are not reflected in performance on tests of executive functions that do not involve multitasking. Currently, a simplified version of the SET is commonly used, the Modified Six Elements Task (MSET).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, these tasks (and various modifications) have been utilized by a number of researchers to investigate executive functioning in normals and various patient populations (e.g., Alderman, Burgess, Knight, & Henman, 2003;Channon & Crawford, 1999;Duncan, Johnson, Swales, & Freer, 1997;Goel & Grafman, 2000;Goldstein, Bernard, Fenwick, Burgess, & McNeil, 1993;Jelicic, Henquet, Derix, & Jolles, 2001;Kafer & Hunter, 1997;Kliegel, McDaniel, & Einstein, 2000;Knight, Alderman, & Burgess, 2002;Levine, Dawson, Boutet, Schwartz, & Stuss, 2000a;Levine et al, in press Levine et al, 1998;Wilson et al, 1998), especially with an eye to rehabilitation planning (e.g., Levine et al, 2000b;Manly, Hawkins, Evans, Woldt, & Robertson, 2002). By now, there are consistent findings supporting the conclusion that these tasks are useful to characterize and quantify executive functioning deficits, and Burgess and his colleagues have made a convincing argument that "strategy application" types of task may be superior to traditional clinical neuropsychological tests (e.g., Wisconsin Card Sorting Test, WCST; Tower of London) at probing "real-world" deficits in executive functioning (Burgess et al, 2006).…”
Section: Introductionmentioning
confidence: 99%